Your new health service (1946)
1946 1946 1940s 2 pages education, such as lectures and films. People are eager to learn how to keep fit and the Association warmly approves this provision. These Health Centres are to be provided, equipped, maintained and staffed (except for general practitioners) by the larger local authorities. General practitioners will be in contract with the local Executive Councils, half of the members of which will be professional — doctors, dentists and chemists representative of their colleagues in the area — while the other half will be appointed by the local health authority and by the Minister. These administrative arrangements — the Regional Hospital Boards responsible for the hospitals, the Local Health Authorities providing Health Centres and clinic services, and the Local Executive Councils with whom general practitioners, dentists and pharmacists are in contract — are cumbrous, and the Association would much have preferred a single administrative body at the Regional level, whose members were democratically elected. We hope, however, that these provisions are to be of a temporary nature until local government as a whole can be reformed. A useful link is supplied by the Hospital Management Committees which will be responsible for the individual hospitals and which will have on them representatives from the three administrative bodies. Doctors The free choice of doctor by patient has been safeguarded, and the doctor's clinical freedom, to use his professional judgment in the treatment of his patient without dictation from any third party, is of course maintained. Doctors at present are very unequally distributed throughout the country, the richer areas having many more doctors proportionally than the poorer districts. Doctors will be paid partly by salary and partly by capitation fees. To produce a fairer distribution, the Bill proposes that doctors in the less popular areas shall receive a higher part-salary, and also that the number of new medical appointments in areas already adequately supplied with doctors should be restricted. Your job We believe that the Bill opens the way to an infinitely better health service than the present worn-out patchwork of services, which is inadequate to the needs of our fellow-countrymen, and we believe that the new health service will be a great improvement both for patient and health worker. But, as the war-time slogan said, "It all depends on me." The health of the people is and must be the concern of the people. Unless the people of this country concern themselves as individuals, as citizens, and as members of organisations, with the proposals of the new service before it becomes law, and with its realisation in practice afterwards, they will not be playing their part, a very important one, in making the service the great instrument for building a healthier Britain that the S.M.A. knows it can become. Support the Government's policy for a healthier Britain. Further copies of this leaflet and other pamphlets may be obtained from the SOCIALIST MEDICAL ASSOCIATION, 35, Long Acre, London, W.C.2 Speedee Press Services Ltd. (T.U. all depts.), 206 Union Street,S.E.1. Extra copies, post free 2/6 per 100, £1 per 1,000 126/TG/377/1/1/34